Support Facilities for Development of Parallel Computational Algorithms - Katkov, S. I.; Pottosin, I. V. (Programming and computer software, 2001)
An approach to the development of parallel programs is described, which is based on algorithmic specification. Functional characteristics and structure of the system that supports the approach and is based on the parallel programming language SuperPascal are suggested. The system is designed for the development of parallel algorithms and for teaching parallel programming.